Using the Health Belief Model to Understand Physical Activity Behavior among Older Adult at Geriatric Care Home - Ahmed Mahdi Niama. Arkan Bahlol Naji (Pakistan Journal of Medical & Health Sciences, 2022)
Background and objectives: PA is a highly successful behavior for preventing and controlling a wide variety of common disorders and it plays an important part in the promotion of a healthy lifestyle as well as the reduction of death rates. The study aimed to The study aimed to assess the physical activity behavior level and to identify the association between study variables and PA. Methods: A descriptive study was conducted at geriatric care home to identify the older adult behavior related to physical activity. The study included a random sample of 70 older adults who were selected from geriatric care home in Baghdad City. The study data were collected by use PASE questionnaire and questionnaire of health beliefs bout physical activity The descriptive statistical measures of frequency and percentage were used. Mean and standard deviation were also used. The linear regression, independent-sample t-test, and one-way analysis of variance were also used. Results: The study showed that the majority of the participants in the study were aged between (60-65) years and most of them were males (65.7%), and the majority are singles (38.6%), with respect to the level of education, less than a half are elementary school graduates (45.7%), and more than two fifth are overweight (42.9%). The study finding indicated that the clear majority have a fair physical activity level (92.9%) followed by a small proportion who enjoy a good physical activity level (7.1%). Conclusion: Researchers concluded that using the HBM to understand PA behavior in general provides a better understanding of how such beliefs can be influenced to improve older adults’ physical activity engagement. The best concept of the health belief model to understand physical activity behavior was cues to action. Recommendations: The researchers recommended designing illustrated indicative programs of physical activity that take into account individual differences between older adults and those who suffer from diseases or disabilities and programs that promote health beliefs and correct misconceptions about physical activity among older adults.